Гибридні нейро-фаззі системи в задачах потокової обробки даних - Сербіна, Д. В.; Валковий, В. В. (ХНУРЕ, 2019)
This work is devoted to modern problems of artificial intelligence. Currently, there is a rapid increase in the amount of stored and processed information, namely texts, in connection with this there is a need to work with big data. Also, the tasks of data mining under conditions when part of the sample is marked up, and part is not and also when the clusters intersect are one of the most important problems of artificial intelligence. Thus, classical algorithms and methods are not enough, and here there is a need to use hybrid neuro-fuzzy systems. This work discusses the method of adaptive sequential clustering and classification was proposed with an unknown method of learning based on an ensemble of fuzzy self-organizing map and vector quantization networks.